Appetitively motivated tasks in the IntelliCage reveal a higher motivational cost of spatial learning in male than female mice - Nigri, Martina; Bramati, Giulia; Steiner, Adrian C.; Wolfer, David P. (Frontiers in Behavioral Neuroscience, 2024)
The IntelliCage (IC) permits assessment of behavior and learning abilities of mice in a social home cage context. In order to overcome water deprivation as aversive driver of learning, we developed protocols in which spatial learning is motivated appetitively by the preference of mice for sweetened over plain water. While plain water is available at all times, only correct task responses give access to sweetened water reward. Under these conditions, C57BL/6J mice successfully mastered a corner preference task with reversal and also learned a more difficult time-place task with reversal. However, the rate of responding for sweetened water decreased strongly with increasing task difficulty, indicating that learning challenge and reduced success in obtaining reward decreased the motivation of the animals to seek sweetened water. While C57BL/6J mice of both sexes showed similar initial taste preference and learned similarly well in simple learning tasks, the rate of responding for sweetened water as well as performance dropped more rapidly in male than in female mice in response to increasing learning challenge. Taken together, our data indicate that male mice can have a disadvantage relative to females in mastering difficult appetitively motivated learning tasks, likely due to sex differences in value-based decision making.